Tratamento periodontal em pacientes portadores de diabetes mellitus tipo I e periodontite: relato de casos. - Camargo, Talles Pinto [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Periodontitis is a chronic inflammatory disease characterized by destruction of dental support tissues. Studies demonstrated that diabetes mellitus (DM) is an important modify factor for development of periodontitis, increasing its susceptibility three times, in addition to having a bidirectional relationship between both. The present study aims to report two clinical cases in which periodontal treatments were performed, according to the need and diagnosis, in patients with DM type I. Patients diagnosed with DM type I were examined at the Oral and Systemic Health clinic of Faculty of Dentistry of Araçatuba, where a detailed anamnesis was performed, complete radiographic examination, general and periodontal clinical examination. A treatment plan was prepared for each case and treatments were carried out. After 90 days, patients were reassessed. Type I DM worsened periodontitis characterized by severe bone loss, loss of clinical insertion leading to loss of dental elements. In addition, the non-surgical periodontal treatment associated with the maintenance and control program was effective in reducing and controlling periodontitis in patients with DM type I.

A periodontite é uma doença inflamatória crônica caracterizada pela destruição dos tecidos de suporte dentário. Estudos indicam que a diabetes mellitus (DM) é um importante fator modificador para o desenvolvimento da periodontite, elevando em três vezes a sua susceptibilidade, além de haver uma relação bidirecional entre ambas. O presente estudo tem como objetivo relatar dois casos clínicos em que foram realizados tratamentos periodontais, de acordo com a necessidade e diagnóstico, em pacientes com DM tipo I. Foram examinados pacientes diagnosticados com DM tipo I na clínica de Saúde Bucal e Sistêmica da Faculdade de Odontologia de Araçatuba, onde foi efetuada uma anamnese detalhada, exame radiográfico completo, exame clínico geral e periodontal. Foi elaborado um plano de tratamento para cada caso e efetuado os tratamentos. Após 90 dias os pacientes foram reavaliados. A DM tipo I promoveu agravamento da periodontite caracterizada por perda óssea severa, perda de inserção clínica levando a perda de elementos dentários. Além disso, o tratamento periodontal não cirúrgico associado ao programa de manutenção e controle foi efetivo para reduzir e controlar a periodontite em pacientes portadores de DM tipo I.
Periodontal treatment in patients with type I diabetes mellitus and periodontitis: case reports.
Keywords: Periodontal diseases; Doenças periodontais; Diabetes mellitus; Relatos de casos